Práticas de gestão e relações de trabalho na produção : estudo de caso em uma empresa estatal - Teixeira, Tadeu Gomes (2010)
The analysis of management practices and labor relations in the Empresa Brasileira de Correios e Telégrafos (ECT) was the goal that guided the research for this dissertation. The focus of analysis runs the various socio-historical contexts in which manage